The use of decorative braces in Jeddah, Saudi Arabia - Ahmed I Masoud; Fatima A Alshams (Wolters Kluwer Medknow Publications, 2020)
OBJECTIVE: To assess the practice of using orthodontic brackets as tooth decorations among dental offices and patients in Jeddah, Saudi Arabia. MATERIALS AND METHODS: The study was a cross-sectional survey using 2 questionnaires. The first included 14 doctor questions where 300 dental offices in Jeddah, Saudi Arabia were contacted by phone. The second questionnaire included 22 patient questions where 50 patients who currently have or have had decorative braces answered the questions online. RESULTS: Out of 250 dental offices that responded, 91 offices (36.4%) answered "yes" to offering decorative braces. Most dentists use metal brackets (96.3%) on both the upper and lower arches (98.8%) and ligate a wire (83.8%) using colored elastomeric ligatures. Out of 50 patients who answered the patient questions, 28 patients (56%) were females and the mean age was 19.84 years (±2.32). 37 (74%) patients reported that their decorative braces were not placed by dentists and mostly by over the counter glue. Finally, 62% reported they were not satisfied, and 84% said they would not recommend getting decorative braces to their family and friends. CONCLUSION: Our results indicate that the use of decorative braces is prevalent, and most are not being placed by dentist. As healthcare providers, we are obliged to educate the public of potential harm that can result when decorative braces are used, to hopefully limit the spread of this unfortunate practice.